The effect of normal electric field on the evolution of immiscible Rayleigh-Taylor instability - Tofighi, Nima; Ozbulut, Murat; Feng, James J.; Yildiz, Mehmet (Theoretical and computational fluid dynamics, 2016)
Manipulation of the Rayleigh-Taylor instability using an external electric field has been the subject of many studies. However, most of these studies are focused on early stages of the evolution. In this work, the long-term evolution of the instability is investigated, focusing on the forces acting on the interface between the two fluids. To this end, numerical simulations are carried out at various electric permittivity and conductivity ratios as well as electric field intensities using Smoothed Particle Hydrodynamics method. The electric field is applied in parallel to gravity to maintain unstable evolution. The results show that increasing top-to-bottom permittivity ratio increases the rising velocity of the bubble while hindering the spike descent. The opposite trend is observed for increasing top-to-bottom conductivity ratio. These effects are amplified at larger electric field intensities, resulting in narrower structures as the response to the excitation is non-uniform along the interface.